2019
DOI: 10.2298/vsp170517098s
|View full text |Cite
|
Sign up to set email alerts
|

The association between the level of physical activity with spinal posture and physical fitness parameters in early adolescence

Abstract: Background/Aim. A low level of physical activity and sedentary lifestyle affects the body posture in adolescents. The aim of this study was to assess the core relation between the level of physical activity and spinal posture as well as physical fitness parameters in 11-14 years old teenagers. Methods. The cross-sectional study included 532 children, aged from 11 to 14 years. The study was carried out at three Lithuanian schools in 2011-2013. The Youth Physical Activity Questionnaire (YPAQ) was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The restrictions to attend school and limited access to after-school sports resulted in significant decreases in PA and increases in sedentary behavior (SB) [9]. That leads to gradual health deterioration in later life and current posture problems [10]. Lithuanian health statistics indicate that as much as 1.6% of children have scoliosis and 3.6% have abnormal posture [11].…”
Section: Introductionmentioning
confidence: 99%
“…The restrictions to attend school and limited access to after-school sports resulted in significant decreases in PA and increases in sedentary behavior (SB) [9]. That leads to gradual health deterioration in later life and current posture problems [10]. Lithuanian health statistics indicate that as much as 1.6% of children have scoliosis and 3.6% have abnormal posture [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to a European study, individuals who engage in low levels of physical activity are more likely to have poor posture. The study found that both a sedentary lifestyle and low physical activity levels have a significant impact on postural parameters [ 37 ]. It appears that engaging in physical activity can enhance body condition through the improvement of muscle strength, balance, flexibility, and range of motion [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, recommendations for increasing physical activity can incorporate different domains such as active transport (e.g., walking to school), participation in unorganized sport or active play [ 8 ], and even breaking up sedentary time with light intensity activity [ 9 ]. While participation in organized sport has been associated with a diverse range of positive outcomes among youth (e.g., enhanced resilience, character development, social skills [ 10 , 11 ]), the health benefits of physical activity (e.g., cardiorespiratory fitness, improved posture) might also be obtained in an unorganized context [ 12 , 13 ]. Thus, both organized and unorganized activity provide beneficial opportunities to increase participation.…”
Section: Introductionmentioning
confidence: 99%